Catastrophic health expenditure and associated factors among adult diabetes patients at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Kibret Mesgie; Asmamaw Atnafu; Tesfahun Zemene Tafere; Nigusu Worku; Banchlay Addis; Asebe Hagos (BMC Health Services Research)
Abstract Introduction Out-of-pocket health expenditures pose a substantial financial burden for millions of people worldwide. Diabetes patients without financial protection often face catastrophic out-of-pocket health expenditure. However, the catastrophic out-of-pocket health expenditure at a 40% threshold have not been well investigated in Ethiopia. Therefore, this study aimed to assess the magnitude of catastrophic out-of-pocket health expenditures and identify associated factors among adult diabetes patients at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. Methods An institutional-based cross-sectional study was conducted on 395 diabetes patients from March 28 to May 15, 2021. Participants were selected using a systematic random sampling technique. Data were collected using a structured questionnaire, entered into Epi-Data version 4.6, and analyzed using STATA version-16. Catastrophic health expenditure was estimated at a 40% threshold of total household non-food expenditure. A multivariable logistic regression model was used to identify factors associated with catastrophic out-of-pocket health expenditures. The adjusted odds ratio (AOR) with a 95% confidence interval (CI) and a p-value < 0.05 was used to determine statistical significance. Result The incidence of catastrophic out-of-pocket health expenditure at the 40% threshold was 51.4% (47.2, 54.2). Age older than 60 years (AOR = 4.67; 95% CI:1.65, 12.06), 3–4 family size (AOR = 2.01; 95%CI:1.04, 3.91), urban residence (AOR = 0.02; 95%CI:0.002, 0.24), 6–10 years of duration of illness (AOR = 1.74;95%CI:1.02, 2.96), and history of admission (AOR = 2.48;95% CI:1.02, 6.00) were significantly associated factors with catastrophic out-of-pocket health expenditures. Conclusions Out-of-pocket health expenditures impose a significant financial burden on diabetes patients and their families. Age above 60 years, a family size of 3–4, urban residence, duration of illness 6–10 years, and history of admission were significantly associated with catastrophic out-of-pocket health expenditure. Therefore, the government should strengthen financial protection mechanisms to protect diabetes patients from catastrophic out-of-pocket health expenditures.